2018
DOI: 10.1007/s11906-018-0862-2
|View full text |Cite
|
Sign up to set email alerts
|

Nurse’s Contribution to Alleviate Non-adherence to Hypertension Treatment

Abstract: Ten clinical studies were identified. The majority of studies reported beneficial effect of nursing intervention on treatment adherence in hypertensive patients. Telephone contacts and home visits were found to be the most effective educational approaches. Although comorbidities are considered to be an important barrier to adherence, there was not enough evidence to elucidate this aspect. Identifying specific factors that affect behavioral change in the setting of a successful intervention was difficult due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
3
0
1
Order By: Relevance
“…Programs that educate people about changing their lifestyles and understanding diseases had higher outcomes for improved blood pressure control and medication adherence. 26 Similarly, in our study, it was observed that blood pressure and cardiovascular risk factors improved through nursing interventions. Likewise, results from another systematic review concluded that digital health interventions led by nurses were more successful than standard treatment in lowering blood pressure and improving self-management in hypertensive patients.…”
Section: Discussionsupporting
confidence: 75%
“…Programs that educate people about changing their lifestyles and understanding diseases had higher outcomes for improved blood pressure control and medication adherence. 26 Similarly, in our study, it was observed that blood pressure and cardiovascular risk factors improved through nursing interventions. Likewise, results from another systematic review concluded that digital health interventions led by nurses were more successful than standard treatment in lowering blood pressure and improving self-management in hypertensive patients.…”
Section: Discussionsupporting
confidence: 75%
“…Despite this varied evidence base, the previous investigation of nurse-led interventions with populations at high CVD risk reported improvements in smoking (Halcomb et al, 2015), alcohol (Platt et al, 2016;Clossick & Woodward, 2014), weight (Sargent et al, 2012), physical activity (Chudowolska-Kiełkowska & Małek, 2020) and medication adherence (Georgiopoulos et al, 2018). (Mitchell et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this varied evidence base, the previous investigation of nurse‐led interventions with populations at high CVD risk reported improvements in smoking (Halcomb et al, 2015), alcohol (Platt et al, 2016; Clossick & Woodward, 2014), weight (Sargent et al, 2012), physical activity (Chudowolska‐Kiełkowska & Małek, 2020) and medication adherence (Georgiopoulos et al, 2018). The limited evidence on dietary interventions to improve nutritional quality and anthropomorphic outcomes compares to previous reviews which found some, yet inconsistent effect in both nurse (McElwaine et al, 2016) and multidisciplinary nutritional interventions in primary care (Mitchell et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…(11,12) In this sense, the literature has indicated that nursing, as part of the health staff, plays a fundamental role in improving this problem, especially through education actions aimed at modifying lifestyles and understanding the disease. (13) Consequently, the aim of this study was to determine the factors associated with adherence to the therapeutic regime (pharmacological and nonpharmacological treatment) in patients with arterial hypertension and T2DM cared for in primary care centers in the city of Bucaramanga in Colombia.…”
Section: Introductionmentioning
confidence: 99%